ROLE OF SPIRITUALITY IN PREDICTING THE GIG WORK SUCCESS - Amy Mardhatillah; Ronald Rulindo; Rosviana Rosida (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2025)
Purpose: This study aims to examine the psychosocial predictors, namely government support, proactive personality, motivation, and spirituality, for the career satisfaction of gig workers in a new era of working. Design/methodology/approach: 323 gig workers across different sectors in Indonesia participated in this study. PLS-Structural Analysis Model (SEM) was performed to examine the hypothesis. Findings: A proactive personality has the highest path score in predicting gig work career satisfaction.  Government Support does not influence the satisfaction of gig work in Indonesia. Originality: This research stands out for its comprehensive examination of factors not previously studied within the Indonesian gig work environment, especially for spirituality. Additionally, the use of SEM analysis methods underscores an exhaustive approach to investigate relationships between the variables studied. The result that government support doesn't significantly impact career satisfaction offers fresh perspectives on the factors influencing gig work success in Indonesia. This study sheds light on psychosocial predictors that could have wider implications for gig workers globally as well as providing insight on the dynamics of gig work.